2020
DOI: 10.1080/13880209.2020.1840597
|View full text |Cite
|
Sign up to set email alerts
|

Latifolin protects against myocardial infarction by alleviating myocardial inflammatory via the HIF-1α/NF-κB/IL-6 pathway

Abstract: Context: The Traditional Chinese herb medicine Dalbergia odorifera T. Chen (Fabaceae), exerted a protective effect on myocardial ischaemia. Latifolin is a neoflavonoid extracted from Dalbergia odorifera. It has been reported to have the effects of anti-inflammation and cardiomyocyte protection. Objective: To investigate whether latifolin can improve myocardial infarction (MI) through attenuating myocardial inflammatory and to explore its possible mechanisms. Materials and methods: Left coronary artery was liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Previous reports have shown that NF-κB, as a key factor in regulating signaling pathway closely related to systemic inflammatory reactions inflammatory, participated in the transcription and modulation of many inflammatory mediators [ 36 ]. Reports have shown that the release of IL-1β and TNF-α, which could be promoted by activated NF-κB activation, stimulated the production of inflammatory factors then resulted in excessive hypertrophy of cardiomyocytes, and finally irreversible damage to myocardial tissue fibrosis [ 37 ]. In this study, we further found that long-term treatment of APS can significantly reduce the expression of all tested pro-inflammatory markers that lead to a notable reduction of inflammatory response in myocardial tissue, thereby significantly reducing the occurrence of inflammatory response, and has a significant advantage over APS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that NF-κB, as a key factor in regulating signaling pathway closely related to systemic inflammatory reactions inflammatory, participated in the transcription and modulation of many inflammatory mediators [ 36 ]. Reports have shown that the release of IL-1β and TNF-α, which could be promoted by activated NF-κB activation, stimulated the production of inflammatory factors then resulted in excessive hypertrophy of cardiomyocytes, and finally irreversible damage to myocardial tissue fibrosis [ 37 ]. In this study, we further found that long-term treatment of APS can significantly reduce the expression of all tested pro-inflammatory markers that lead to a notable reduction of inflammatory response in myocardial tissue, thereby significantly reducing the occurrence of inflammatory response, and has a significant advantage over APS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the volatile oil of DO increased the absorbance of major ingredients in QSYQ 33 . Recently, latifolin, as a newly extracted flavonoid, was shown to protect against myocardial infarction and oxidative stress-induced senescence 34,35 36 . Hydroxyobtustyrene, a cinnamyl phenol, exerted an anti-hypoxia effect on neuronal cells 37 .…”
Section: Dalbergia Odorifera T Chen Is Indigenous To Hainanmentioning
confidence: 99%
“…For example, latifolin and astragaloside IV can regulate expression of NF-κB. The former inhibits the inflammatory response of macrophages by regulating the HIF-1α/NF-κB/IL-6 signaling pathway, and the latter regulates TLR4/NF-κB/PPAR signaling-mediated energy biosynthesis to alleviate LPS-induced myocardial injury [ 119 , 120 ]. In addition, morroniside, NR4A3 and metformin can suppress expression of NF-κB.…”
Section: Treatmentmentioning
confidence: 99%